Cassapro in broiler ration : Interaction with rice bran - I. Putu Kompiang; A.P. Sinurat; T. Purwadaria; J. Darma; Supriyati . (Indonesian Center for Animal Research and Development (ICARD), 1995)
A three by three factorial experimental design (cassapro levels 0, 5 and 10% x rice bran levels 0, 21 and 42%) was employed to study the effect of cassapro and rice bran and their interaction on boiler performance. All rations were formulated to be isonutrients . Each ration was fed to 40 three days old chicks, divided into 4 cages (10 birds/cage). Feed and water were given ad libitum during the 4 weeks trial . Feeding cassapro significantly (P<0 .05) improved body weight gain, with no significant effect on feed conversion ratio (FCR). Rice bran significantly (P<0 .001) reduced body weight gain and caused poorer FCR (P<0 .01) . There was a significant interaction effect of cassapro and rice bran on body weight gain (P<0.01) as well as FCR (P<0 .001) . It is concluded that cassapro contained some factors, which are most likely digestive enzymes, which enhhance digestibility of rice bran .